THE EFFECT OF EXPERIENTIAL LEARNING-BASED SCIENCE INTEGRATED LEARNING ON STUDENTS' INTERPERSONAL COMMUNICATION ON HEAT AND TEMPERATURE MATERIALS - Dinda Indrianingrum; Lia Yuliati; Nasikhudin, Nasikhudin (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to analyze the effect of a Science Integrated Learning model based on Experiential Learning on students' interpersonal communication skills in the context of heat and temperature material. A mixed methods approach with a sequential explanatory design was employed. In the quantitative phase, an experimental design was used involving both control and experimental groups. The sample consisted of 66 high school students selected through purposive sampling. Instruments included a student questionnaire and interview guidelines. Quantitative data analysis were analyzed using an independent t-test. The results showed that students who participated in the Science Integrated Learning model based on Experiential Learning a significantly greater improvement in interpersonal communication compared to students who just with the Science Integrated Learning method (p <0.05). In the qualitative phase, in-depth interviews were conducted to explore factors that supported the effectiveness of the model. The qualitative findings revealed that students experienced notable improvements in communication, particularlyin the aspects of openness, empathy and supportiveness. These findings indicate that the experience-based learning positively influences students' interpersonal communication skills. This research offers a novel integration of the Science Integrated Learning model with the Experiential Learning approach to enhance students’ interpersonal skills while learning physics. Unlike previous studies that focused primarily on cognitive outcomes or applied these models independently, this study uniquely combines both to address students’ conceptual understanding and social communication skills simultaneously